Faces of tuberculosis: a riveting exploration into demographics and health profiles of patients in rural Jharkhand - Bagti, Putul; Jagadeesh, Bharath; Tirkey, Neelima (International Journal Of Community Medicine And Public Health, 2024)
Background: Tuberculosis is a pressing health concern in Jharkhand, India, claiming 13,000 lives annually. This retrospective study, conducted by Tata steel foundation, delves into the health and sociodemographic profiles of TB patients in the tribal-dominated East Singhbhum district. Noteworthy findings include risk factors such as Anaemia, Diabetes compounded by challenges like limited access to health facilities. TSF’s initiatives, including Nikshay Mitra and support for NTEP, are crucial components in addressing TB in the region. Methods: A retrospective study (September to November 2023) analyzed records from TSF’s DOTS centre in East Singhbhum. Data from 2019-2023 were extracted and analyzed using descriptive statistics. Results: The average age of 293 patients was 37.36±14.97 years, with 83.6% belonging to Scheduled Tribes. Sputum analysis revealed a 61.4% positive rate for Acid Fast Bacillus. Notably, 85.3% completed treatment, and abnormal chest radiographs were observed in 99.3% of cases. Conclusions: The proposed way forward outlines actionable strategies to further strengthen TB awareness, focus on challenging districts, engage communities, and collaborate with government health centers. Regular research and monitoring, coupled with periodic impact assessments, will be crucial for adapting and refining interventions in alignment with the dynamic landscape of TB prevalence.